2003
DOI: 10.1128/jcm.41.6.2623-2628.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Clinical Isolates of Acremonium strictum Determined during an Investigation of a Fatal Mycosis

Abstract: Primarily saprophytic in nature, fungi of the genus Acremonium are a well-documented cause of mycetoma and other focal diseases. More recently, a number of Acremonium spp. have been implicated in invasive infections in the setting of severe immunosuppression. During the course of routine microbiological studies involving a case of fatal mycosis in a nonmyeloablative hematopoietic stem cell transplant patient, we identified a greater-than-expected variation among strains previously identified as Acremonium stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…Since there are close morphological similarities between A. strictum and A. kiliense, it is possible that these cases were actually caused by the latter species or by some other species of the genus. In this context, attention may be drawn to two recent case reports (9,27) where sequenced isolates identified as A. strictum in fact belonged to the Acremonium sclerotigenum-Acremonium egyptiacum group (30). In an attempt to differentiate A. kiliense from A. strictum, Perdomo et al (30) observed that isolates of A. kiliense form unicellular chlamydospores and adelophialides (reduced forms of phialides without a basal septum) in the vegetative or substrate hyphae (not in aerial hyphae) when grown on oatmeal agar at 24°C for about 2 weeks.…”
Section: Case Reportmentioning
confidence: 99%
“…Since there are close morphological similarities between A. strictum and A. kiliense, it is possible that these cases were actually caused by the latter species or by some other species of the genus. In this context, attention may be drawn to two recent case reports (9,27) where sequenced isolates identified as A. strictum in fact belonged to the Acremonium sclerotigenum-Acremonium egyptiacum group (30). In an attempt to differentiate A. kiliense from A. strictum, Perdomo et al (30) observed that isolates of A. kiliense form unicellular chlamydospores and adelophialides (reduced forms of phialides without a basal septum) in the vegetative or substrate hyphae (not in aerial hyphae) when grown on oatmeal agar at 24°C for about 2 weeks.…”
Section: Case Reportmentioning
confidence: 99%
“…Eight KT isolates (i.e., K5217-2-2, K5217-2-3, K5225-6-1, K5225-13-3, K5225-14-3, K5225-15-1, K5225-19-1, and K5229-19-2) were placed in the cluster represented by Acremonium strictum (Nectriaceae), including the ex-type strain CBS 346.70 (isolated from Triticum aestivum leaf) of A. strictum (AY138483; see Table 3 in Novicki et al 2003) and A. strictum AY 138484 and AY 138485 (isolated from human blood; Novicki et al 2003). Although cultural and morphological characteristics of these KT isolates agreed with those of A. strictum (Gams 1971;Domsch et al 2007), additional molecular phylogenetic data are needed to identify KT isolates to species.…”
Section: Resultsmentioning
confidence: 99%
“…A. strictum CBS 102295 was not identified, and this might be due to genetic diversity among isolates of the species. Novicki et al (39) found a greater-than-expected variation among strains previously identified as A. strictum. In sequence analyses of the ITS regions and the D1/D2 variable domain of the 28S ribosomal DNA, five clinical isolates phenotypically identified as A. strictum were found to have Ͻ99% similarities to the A. strictum type strain (CBS 346.70) at the ITS and 28S loci.…”
Section: Discussionmentioning
confidence: 99%